Character Education of Students in Pondok Modern Darussalam (PMD) Gontor in Thomas Lickona Theory Perspective - Elyunusi, Melikai Jihan; Rusijono, Rusijono; Izzati, Umi Anugerah (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
The purpose of this study was to determine the character of the santri in PMD Gontor Ponorogo. This research method uses qualitative methods. The data were obtained from the process of character education for students at this Pondok. Using and analyzed Thomas Thomas Lickona's theory in the book Educating for Character: How Our Schools Can Teach Respect and Responsibility and Character Matters. The results of the study show that: 1) Pancajiwa is the values ​​developed by PMD Gontor including five values: sincerity, simplicity, self-help, Islamic brotherhood, and freedom. 2) The values ​​that shape the character of modern Islamic boarding schools are transformed into the learning process, the formation of Islamic boarding school culture, collaborative curriculum activities, and extracurricular activities. 3) Thomas Lickona revealed that there are several important values ​​to be instilled in students, namely as follows: a. Honesty, b. Tolerance, c. Wisdom, d. Self-discipline, and e. Courage. While the character education strategy according to Thomas Lickona, assumes the triad of personality formation, namely the concept of morality (moral knowledge), moral attitudes (emotional ethics), and ethical behavior (ethical behavior). Thus, the process of character education must be seen as a conscious and planned effort, not an effort that occurs by chance.